Peran United Nations International Children’s Emergency Fund (UNICEF) dalam Memberikan Perlindungan Hak Anak Sebagai Korban Perekrutan Tentara Bersenjata di Republik Demokratik Kongo - Pasha, Aura Alifia Kamilla; Yustitianingtyas, Levina (Wajah Hukum, 2024)
This legal research focuses on the issue of the extent of UNICEF’s role in protecting the rights of children who are victims of exploitation and abuse, on of which is that occur in conflict areas Republic Democratic of Congo. One of the phenomena that occurs is the recruitment of armed soldiers which occurs among children. This case of child soldiers that occurred in the Republic Democratic of Congo involved various armed Rally Constitutional Democratic (RCD) parties in fighting pro government parties and creating political grudges that could attract children in this country to take part in the conflict as child soldiers. This legal issue in this research discusses the role of UNICEF in providing protection for children recruited as armed soldiers in the Republic Democraic of Congo from the perspective of International Humanitarian Law. Research methods juridical normative with a descriptive approach to invitation regulations based on primary, secondary, and tertiary data sources. This results of this research show that children as victims of exploitation by armed soldiers have not received optimal treatment because UNICEF is experiencing obstacles in resolving children’s rights in the Republic Democratic of Congo.